RESILIENCE OF PARTICIPANTS OF THE EDUCATIONAL PROCESS IN WAR CONDITIONS: CHALLENGES AND PSYCHOLOGICAL RECOVERY (Innovative professional education, 2025)
The article presents theoretical and practical aspects of highlighting the problem of building resilience among teachers and students of Professional Pre-Higher Education. Examples of effective psychological recovery by using strategies from the American Psychological Association are given.
Keywords: research, resilience, adaptation, psychological recovery, professional assistance